NUSXA KO’CHIRISH QURILMASI SIYOXI TARKIBIDAGI XROM (III) IONINI ORGANIK REAGENTLAR YORDAMIDA ANIQLASH (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, research on the analytical methods of determining the chromium (III) ion contained in the black ink used in the copying machine used in our daily life, determining their existing properties and using them is described. It was determined that the average amount of chromium (III) ion in black ink is equal to 0.002 g.